Smart Antenna Array for Optimal Electromagnetic Energy Capture - Cumbajín, Myriam (2023)
Smart antennas are currently one of the most exploited fields in terms of wireless networks, allowing high data transmission capacities, this is achieved by focusing the radiation on the desired direction and adjusting to the environment and conditions in which communications are developed. Smart antennas employ a set of radiating and emitting and combining elements organized in the form of arrangements connected at a common point to guarantee the required power, the signals from these elements are combined to form a moving beam pattern that follows a pattern determined by the user or designer. The consumption of energy within communication systems is considered a big problem and a challenge when carrying out implementations in media where the storage or recharging of the end terminals is complicated by their location, this trend grows with the presence of the Internet of the IoT things, where it is directly dependent on the construction of a large wireless network that allows everything to be interconnected, for this reason there are investigations in the 2.4 and 5.8 GHz bands and represents future work for the 5th Generation (5G) cell phone. The great possibility of collecting electromagnetic energy from densely populated urban areas becomes a great renewable source of power for communication devices for both existing Wi-Fi technology and new technologies such as the 5G network.